An Importance-Performance Analysis of Accessible Tourism: A Tourist and Resident Perspective with Empirical Insights from Phuket - FUCHS, Kevin (Journal of Environmental Management and Tourism, 2024)
The fundamental principle of accessible tourism revolves around advocating for the inclusion and empowerment of individuals with disabilities, aiming to facilitate complete engagement for individuals with disabilities within tourism experiences. Previous research established a five-dimensional exploratory framework revealing several barriers that prevent Phuket Island from fully engaging in accessible tourism and increasing its global market share in this emerging market segment. This study sought to build upon previous findings by empirically investigating these barriers through the utilization of the importance-performance analysis method. Methodologically, survey data was collected from 391 tourists and residents in Phuket. The findings align with previous research, highlighting the preparedness of Phuket's international airport, diverse luxury accommodation options, and internationally accredited medical facilities. These elements stand out as exemplary in meeting the needs of accessible tourism. Conversely, the present infrastructure, insufficient transportation systems, and limited recreational options pose significant challenges, marking them as pivotal bottlenecks. The article discusses practical implications to rectify these limitations and advances the discussion about using the importance-performance analysis as a managerial tool to evaluate the quality of tourism experiences in the context of accessible tourism.